PENGUJIAN APLIKASI TRANSAKSI PERDAGANGAN MENGGUNAKAN BLACK BOX TESTING BOUNDARY VALUE ANALYSIS - Agus Utomo; Yusuf Sutanto; Erna Tiningrum; Eko Meiningsih Susilowati (Politeknik Ubaya, 2020)
The information system is one of the needs that is often used to facilitate human work. Jobs that often use information systems are office jobs, both in government and private agencies. Companies generally need an information system to simplify work such as creating cooperation documents, contract documents with external parties, as well as to help make monitoring and evaluation sheets for internal management. Like a system, to be able to store and display data as it should. Information system testing is needed in order to know the shortcomings of a system. The drawbacks of a system can be in the form of features that don't work properly or there are differences between the features expected and the features available. One of the tests of information systems is testing the Black Box method system by means of Boundary Value Analysis. Boundary Value Analysis is a method of testing by determining the lower and upper limit values ​​of the data to be tested. This test is carried out on the function of adding new goods data to the trade transaction application. The test results are still lacking when validating the data entered into the system, causing the data stored in the database to not match what was expected. The results of this test can be an input to improve the application so that the eligibility requirements of the information system are better in accordance with the expected data entered into the system.